TRANSPARENCY OF INFORMATION AS A FORM OF CONSUMER PROTECTION IN FINANCIAL SERVICES INDUSTRY (CASE STUDY ON LIVIN”™ BY MANDIRI MOBILE BANKING USER) - Abrianto, Heri; Hadiati Farhani, Nuraeni; Cipta Bidhari, Sandhika; Hamonangan Pasaribu, Edward Hot; Neila, Neila (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2024)
During the pandemic, banking services are required to be more accommodating to customer needs. One way to meet these demands is that banks must be able to optimize the use of their technology. As a state-owned bank, Bank Mandiri has started digital transformation with the launch of Livin' by Mandiri. This is ensured by prioritizing ease of access, innovation and data security. Banking digitalization has also proven to be important in implementing Bank Mandiri's sustainability initiatives. Digitalization makes it easier to support economic recovery during the pandemic, encourage the development of MSMEs, increase financial inclusion for marginalized communities. The problem that will be formulated in this research is the implementation of information transparency in relation to consumer protection. This research uses a quantitative analysis method based on the results of a questionnaire that will be distributed to students in Politeknik Negeri Jakarta who use the Livin' by Mandiri application. The research independent variable is information transparency and the dependent variable is consumer protection. The research results show that transparency of banking product information, transparency of consumer personal data have a significant impact on consumer protection.